Physical characterization of the Guadiana Estuary using a 3D model - Calero Quesada, María Concepción; Delgado, Javier; Garel, Erwan; García-Lafuente, Jesús; Martins, Flavio; Moreno-Navas, Juan (My University, 2016)
Guadiana estuary is an intertidal estuary situated in SW of Iberian Península, the latest 50 Km of which constitutes the natural border between Spain and Portugal. Tidal influence extends to about 80 Km upstream. The Guadiana River presents a high seasonal irregularity with wet winters and dry summers. A 3D hydrodynamic model based on the MOHID System has been developed to study the hydrodynamics of the Guadiana Estuary. The model has been validated by comparison the output with in situ data measurements in several points along the estuary.
Keywords: Ecología de estuarios; Gulf of Cádiz; 3D numerical model; Estuary; Guadiana